Counteractions of a Novel Hydroalcoholic Extract from Lens Culinaria against the Dexamethasone-Induced Osteoblast Loss of Native Murine Cells - Marina Antonacci; Jacopo Raffaele Dibenedetto; Fatima Maqoud; Gerardo Centoducati; Nicola Colonna; Francesco Leonetti; Domenico Tricarico (Cells, 2022)
The cytoprotective effects of a novel hydroalcoholic extract (0.01–5 mg/mL) from Lens culinaria (Terre di Altamura Srl) were investigated within murine native skeletal muscle fibers, bone marrow cells, and osteoblasts, and in cell lines treated with the apoptotic agent staurosporine (2.14 × 10−6 M), the alkylating drug cisplatin (10−4 M), the topoisomerase I inhibitor irinotecan (10−4 M), the antimitotic pro-oxidant doxorubicin (10−6 M), and the immunosuppressant dexamethasone (2 × 10−6 M). An amount of 10g of plant material was used to obtain a 70% ethanol/water product, following two-step extraction, evaporation, lyophilization, and storage at −20 °C. For the murine osteoblasts, doxorubicin reduced survival by −65%, dexamethasone by −32% and −60% after 24 and 48 h of incubation time, respectively. The extract was effective in preventing the osteoblast count-reduction induced by dexamethasone; it was also effective at preventing the inhibition of mineralization induced by dexamethasone. Doxorubicin and cisplatin caused a significant reduction in cell growth by −77% for bone marrow cells, −43% for irinotecan, and −60% for dexamethasone, but there was no evidence for the cytoprotective effects of the extract in these cells. Staurosporine and doxorubicin caused a fiber death rate of >−40% after 18 and 24 h of incubation, yet the extract was not effective at preventing these effects. The extract was effective in preventing the staurosporine-induced reduction of HEK293 proliferation and colony formation in the crystal violet DNA staining and the clonogenic assays. It was also effective for the cisplatin-induced reduction in HEK293 cell proliferation. The extract, however, failed to protect the SHSY5Y neurons against cisplatin and irinotecan-induced cytotoxicity. A UV/VIS spectroscopy analysis showed three peaks at the wavelengths of 350, 260, and 190 nm, which correspond to flavonoids, proanthocyanins, salicylates, and AA, constituting the extract. These data suggest the possible development of this extract for use against dexamethasone-induced bone loss and renal chemotherapy-induced damage.